E-commerce transactions, the installed base of credit cards, and the potential mobile E-commerce adoption - Madden, G.; Banerjee, A.; Rappoport, P.; Suenaga, Hiroaki (Routledge, 2016)
Mobile e-commerce (m-commerce) relaxes consumers’ temporal and geographic purchasing constraints and encourage the establishment of omnichannel markets. It is often argued that rapid increase in smartphone penetration is the primary driver of m-commerce adoption, whereas others contend that early adoption of m-commerce applications are mostly by “relatively heavy” Internet commerce users. Brynjolfsson et al. (2013) argue that rapid increase in smartphone penetration is the primary driver of m-commerce adoption, whereas Einav et al. (2014) contend that early adoption of m-commerce applications are mostly by ‘relatively heavy’ Internet commerce users. This article explores strength of the influences within a nested multiple-service framework, where the reduced-form econometric analysis allows for interdependency between m-commerce and e-commerce services, and the installed base of credit cards. The results reveal a complex situation in which credit cards facilitate e-commerce services, whereas m-commerce adoptions are driven by prior e-commerce and online transaction activity. Also, higher respondent incomes are negatively associated with proposed m-commerce adoption. Surprisingly, privacy concerns do not affect proposed adoption independently; however, an interaction term suggests privacy remains an adoption barrier for the older persons.